Implementasi Metode Sima’I Tahfidz Al-Qur’an Dalam Meningkatkan Kemampuan Hafalan Al-Qur’an - Mayang Ika Wardani; Aulia Ayu Rohayah (Turabian: Jurnal Pendidikan Islam, 2023)
The purpose of this study is to analyze the Implementation of the Sima'an Tahfidz Al-Qur'an Method in improving student memorization. This research was motivated by the decline in student memorization at SDIT Al-Barkah. In this case, it is necessary to have knowledge to improve the memorization of the Qur'an for students at SDIT Al-Barkah. The sima'an method is a method that is easy to use in reciting the Qur'an and is easy to practice in learning the tahfidz of the Qur'an. So that it can be a source of insight for teachers or guides of memorization of the Qur'an. The formulation of the problem in this study is how to improve the memorization of the Qur'an in students who have difficulty memorizing. From the big question above, there are several more questions, namely: How is the Implementation of the Siama'an Tahfidz Al-Qur'an method in improving the memorization of the Qur'an on BTAQ learning at SDIT Al-Barkah and what are the supporting and inhibiting factors in implementing the Qur'an tafidz method in improving the memorization of the Qur'an of students at SDIT Al-Barkah. This study used school research using observation techniques, interviews, and data analysis. The data technique used in this study is qualitative data. By using observation methods, interviews, and data analysis, researchers get the data they need. The results of this study show that: the Qur'an tahfidz sima'an method can make it easier for students to memorize the Qur'an and can improve students memorization of the Qur'an. By applying this method, students become excited in memorizing the Qur'an because it is very easy to apply in everyday life.